Preparation and Characterization of Bulk and Alumina Supported Hausmannite Nanoparticles - Deraz, N.M.; A. Abdeltawab, Ahmed; S. Al-Deyab, Salem (Asian Journal of Chemistry, 2014)
Bulk and alumina supported hausmannite Mn3O4 nano-particles were prepared by glycine assisted combustion method with different amounts of glycine. Scanning electron micrographs, energy dispersive X-ray and X-ray diffraction measurements display the structural and morphological properties of alumina and bulk and alumina supported hausmannite Mn3O4 nano-particles. The as prepared systems are spongy, homogeneous and fragile. XRD results showed alumina in all samples is amorphous phase. However, the produced manganese oxide is hausmannite Mn3O4 with spinel structure. The change in the amount of glycine and using of alumina carrier led to a significant change in the crystallite size, lattice constant and unit cell volume of Mn3O4 phase.